Sede mundial de Adidas - Bolles + Wilson (2001)
Campus deportivo. Herzogenaurach, Alemania 1999. Concurso
Keywords: BOLLES, JULIA; WILSON, PETER; ALEMANIA; CONCURSOS; CENTROS DEPORTIVOS; ARQUITECTURA DEPORTIVA; BOLLES + WILSON